-3y+7=-4y+3

Simple and best practice solution for -3y+7=-4y+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3y+7=-4y+3 equation:


Simplifying
-3y + 7 = -4y + 3

Reorder the terms:
7 + -3y = -4y + 3

Reorder the terms:
7 + -3y = 3 + -4y

Solving
7 + -3y = 3 + -4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4y' to each side of the equation.
7 + -3y + 4y = 3 + -4y + 4y

Combine like terms: -3y + 4y = 1y
7 + 1y = 3 + -4y + 4y

Combine like terms: -4y + 4y = 0
7 + 1y = 3 + 0
7 + 1y = 3

Add '-7' to each side of the equation.
7 + -7 + 1y = 3 + -7

Combine like terms: 7 + -7 = 0
0 + 1y = 3 + -7
1y = 3 + -7

Combine like terms: 3 + -7 = -4
1y = -4

Divide each side by '1'.
y = -4

Simplifying
y = -4

See similar equations:

| 14x^2-17xy+5y^2= | | 64-49y^2=0 | | 8x-4=6x-6 | | 10-6m=-104 | | 2x^2+7x-2=x^2+2x | | 4x^2-xy-3y^2= | | -10=10k-90 | | q+2=5 | | -103=-9x-13 | | x^2+8x+68=0 | | 9(9x+4)= | | x+(x+4)=2(x-3x) | | 10x^2-5x-5= | | 8-x+1=6 | | x+3x=2(x-4) | | 4y^2+20Y=0 | | 3(7x-5)= | | x+4=2(x-3x) | | p^2+5p=6 | | 2b^2=9b+5 | | 5(6+x)=85 | | x^2=4-7x | | 3(x^2-x)-4(x^2+x)=-3(x+1)-4(x+2) | | 3r^3+18r^2=21r | | 5x=32 | | 75y^2-147=0 | | 2x^2+9x=8 | | X^2-21x+54=0 | | 3x+6=-21 | | Z^2-21z+54=0 | | A^2-25a=0 | | 3x^2-42x-216=0 |

Equations solver categories